Indian culture: an introduction - Sinha, Jai B. P. (Henry Stewart Talks, 2011)
Indian culture, Long history, Pluralistic worldview, Continuity of traditions, Palimpsest, Hindu religion, Metonymic thinking, Oral tradition, Synthesizing mindset, Coexistence of opposite orientations, Collectivist and individualist, Hierarchical, Holistic, analytic, and emotional, fatalist, harmonious and violence prone, spiritualist and materialist, Context sensitive, Variable, Strategy for managing